A comparative analysis of sleep spindle characteristics of sleep-disordered patients and normal subjects - Chen, Chao; Wang, Kun; Belkacem, Abdelkader Nasreddine; Lu, Lin; Yi, Weibo; Liang, Jun; Huang, Zhaoyang; Ming, Dong (Frontiers in Neuroscience, 2023)
Sleep spindles, the hallmark of stage N2 of sleep, are characterized by a fusiform morphology. Spindles differ in density, amplitude, and frequency, and these variations reflect different physiological processes. Sleep disorders are characterized by difficulty in falling asleep and maintaining sleep. In this study, we compared the spindle characteristics of sleep-disordered subjects and normal subjects (those without any sleep disorder) to assess the spindle activity during human sleep. Specifically, we scored 30 subjects (20 sleep-disordered, 10 normal) on the Pittsburgh Sleep Quality Index and then analyzed the association between their sleep quality scores and spindle characteristics, reflecting the effect of sleep disorders on spindle characteristics. A p-value < 0.05 was considered statistically significant. We found a significant correlation between the sleep quality score and spindle density (p = 1.84×10−8). We, therefore, concluded that the higher the spindle density, the better the sleep quality. The correlation analysis between the sleep quality score and mean frequency yielded a p-value of 0.667, suggesting that the spindle frequency and sleep quality score were not significantly correlated. The p-value between the sleep quality score and spindle amplitude was 1.33×10−4, indicating that the mean amplitude of the spindle decreases as the score increases, and the mean spindle amplitude is generally slightly higher in the normal population than in the sleep-disordered population. The normal and sleep-disordered groups did not show obvious differences in the number of spindles between symmetric channels C3 and C4 and F3 and F4. The difference in the density and amplitude of the spindles proposed herein can be a reference characteristic for the diagnosis of sleep disorders and provide valuable objective evidence for clinical diagnosis.